“Who is Crazy in this Country?” Verbalizing Emotions in Political Discourse - Palašić, Nikolina (Poznańskie Studia Slawistyczne, 2015)
In the center of our interest is the use of emotion-marked linguistic resources in the public discourse, and more specifically in the Croatian political public sphere. As politics is traditionally considered a place from chich emotions should be expelled and where rationality is that characteristic which comes first in state administration, the question is where do political statements draw their emotional value and what is its role, i.e. if it occurs by accident or it is based on the speaker’s intention. In this paper, we will try to answer those questions, taking into account previous reflections on emotions.